Respon Masyarakat Terhadap Pantai Syariah Pulau Santen di Kelurahan Karangrejo Banyuwangi - Nawal Ika Susanti (Institut Agama Islam Darussalam Blokagung Banyuwangi, 2018)
The purpose of this study to determine the extent of the application of the concept of Islamic tourism in Santen Island and also to find out the response form in the Santen Island. Data collection method used is the technique of in-depth interview, documentation and observation. While the data analysis technique using the interactive model, which consists of three components: data reduction, data presentation, drawing and testing data. The findings in this study include the application of the concept of Islamic tourism in Santen Island is still not optimal. Public response was positive at 65% of the public has a positive perception, 45%, have a positive attitude, 77.5% indicated that participation is positive. In terms of visitors by 74% of the visitors to know about the concept of sharia travel, 67% of visitors consider aspects of clean and unclean before traveled on the beach sharia, 47% of visitors said existing facilities are adequate Santen Island, 60% of visitors considered that the separation of male and women place have not been in accordance with the concept of Islamic tourism. While the impact of the economic field include an increase in local economies and reduce unemployment on the island of Santen. The impact of the field of education, namely namely the Early Childhood Education Park while the impact on social and cultural sectors has yet to be seen clearly, but the direction to change is already starting to look good in terms of language and dress.